2011
DOI: 10.1093/infdis/jir664
|View full text |Cite
|
Sign up to set email alerts
|

Limited Geographical Origin and Global Spread of Sulfadoxine-Resistant dhps Alleles in Plasmodium falciparum Populations

Abstract: The infrequent selection of parasites highly resistant to sulfadoxine and the subsequent migration of resistant lineages from Asia to Africa are similar to the patterns observed in chloroquine and pyrimethamine resistance. These findings strongly suggest that the global migration of resistant parasites has played a decisive role in the establishment of drug-resistant P. falciparum parasites, and that similar patterns may be anticipated for the spread of artemisinin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 47 publications
5
78
0
1
Order By: Relevance
“…A large-scale study in Africa has shown that only five resistant lineages were observed in mild-to moderate-resistant parasites (parasites harboring one or two substitutions in DHPS) (69). Most recently, we have obtained evidence for the intercontinental spread of sulfadoxine resistance from Southeast Asia to East Africa (13). In that study, dhps alleles and linked microsatellite haplotypes were determined in sulfadoxine-resistant P. falciparum isolates obtained from Asia, the Pacific Islands, Africa, and South America.…”
Section: -3 Sulfadoxinementioning
confidence: 81%
See 3 more Smart Citations
“…A large-scale study in Africa has shown that only five resistant lineages were observed in mild-to moderate-resistant parasites (parasites harboring one or two substitutions in DHPS) (69). Most recently, we have obtained evidence for the intercontinental spread of sulfadoxine resistance from Southeast Asia to East Africa (13). In that study, dhps alleles and linked microsatellite haplotypes were determined in sulfadoxine-resistant P. falciparum isolates obtained from Asia, the Pacific Islands, Africa, and South America.…”
Section: -3 Sulfadoxinementioning
confidence: 81%
“…Several recent studies on dhps alleles and microsatellite haplotypes closely linked to the dhps gene have revealed the putative geographical origins and spread of sulfadoxine-resistant P. falciparum isolates (11,13,38,40,68,69) (Fig. 5C).…”
Section: -3 Sulfadoxinementioning
confidence: 96%
See 2 more Smart Citations
“…Some patient samples had mixed Pfcrt-76K/T genotypes. A previous study by Mita et al 40 showed that patients with mixed infections had sensitive in vivo CQ response.…”
Section: Discussionmentioning
confidence: 95%